Isolation and evaluation of multi-functional properties of lactic acid bacteria strains derived from canine milk - Liu, Yunjiang; Zeng, Yueyan; Chen, Li; Xin, Jialiang; Zhong, Zhijun; Liu, Haifeng; Fu, Hualin; Zhou, Ziyao; Peng, Guangneng (Frontiers in Veterinary Science, 2024)
IntroductionLactic acid bacteria (LAB) are Gram-positive bacteria that produce lactic acid during fermentation, with some strains enhancing host health by modulating the gut microbiota, boosting immune responses, and reducing inflammation.MethodsIn this study, 6 LAB strains were isolated from two dog milk samples, and their probiotic properties were comprehensively evaluated. The evaluation included growth properties, stress resistance, antipathogen activity, adhesion activity, safety assessment, antioxidant capacity, and prebiotic metabolites assessment.ResultsIn comparison to the control strain Lactobacillus rhamnosus LGG, all 6 LAB isolates exhibited favorable probiotic properties. Additionally, the results of the antioxidant tests indicated that these strains demonstrated high tolerance to 0.5 mmol/L H2O2 and exhibited significant scavenging abilities for the free radicals 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) and hydroxyl (OH−). Furthermore, the 6 LAB isolates were found to produce elevated concentrations of prebiotic metabolites, including exopolysaccharides (EPS), γ-aminobutyric acid (GABA), and bile salt hydrolase (BSH).DiscussionThis study presents a comprehensive analysis of LAB isolates derived from canine milk. These isolates exhibited multifunctional properties, with strain L221 performing the best overall, making it a promising candidate for probiotic use in dogs.